The effect of foliar spraying with seawinner extract and potassium humate on some growth and productivity characteristics of tobacco (Nicotiana tabacum L. cv. Shak al-Bint) (Latakia University Journal -Biological Sciences Series, 2025)
The experiment was carried out in the village of Bsaisin in the Jableh region- Latakia governorate on the Syrian coast, during the 2023 agricultural season. Seedlings of tobacco (Nicotiana tabacum L. cv. Shak al-Bint) were cultivated in experimental plots according to a randomized complete block design (RCBD) and in three replicates. The objective of this research was to study the effect of foliar spray treatments with seawinner extract (Alga21ST®) AS (0, 0.75, 1.5 and 2.25 g/L) or potassium humate (GRO-GREEN K-humate) PH (0, 1, 2 and 3 g/L), and the combined effect of spraying with both organic fertilizers on some growth and production characteristics of the studied tobacco variety. So, Plant height (cm), total leaf area (cm2), net photosynthetic rate (mg/cm2/day), leaf specific weight (mg/cm2), total leaf content of chlorophyll, carotenoids, polyphenols, proline (µg/g wet weight), and productivity (green and dry leaf yield (kg/1000 m2)) were measured. The results showed that foliar spraying with seawinner extract, especially at concentrations (1.5 and 2.25 g/L), and spraying with potassium humate (1 and 2 g/L) led to a significant increase (P